Propuesta metodológica para el análisis del riesgo en la construcción de túneles (2017)
"This project proposes a quantitative methodology, which first takes into account the quantification of the probability of occurrence of the event or risk with the Bayesian Analysis and their respective networks, in order to look at the interaction of their causes and their repercussion in the Final event analyzed. Then the impact on the duration of the activity is found to observe how much this nominal duration can affect. At the end is the value of risk (relationship between probability and impact). In this last step the Monte Carlo simulation technique is used, resulting in a value in days of possible forecast, which should be taken into account as additional value in the milestones of the critical route of the programming." -- Tomado del Formato de Documento de Grado.